Rumah Batik Riau Dengan Pendekatan Arsitektur Eco-Tech Di Pekanbaru - Mutia Dwi Alicia; Mira Dharma Susilawaty; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Batik was previously only famous on the island of Java, but over time, batik has spread throughout Indonesia and can be enjoyed by various groups. UNESCO's acknowledgment of batik culture makes batik must be maintained its existence and sustainability. Riau Province also participates in preserving batik and has different batik patterns and motifs from other regions of the archipelago. The motifs and characteristics of Riau batik are adopted from Riau Malay culture, marked by the use of striking colors, flora motifs in Riau, perpendicular grooves, and having a meaningful philosophy. However, there are still many Riau people who do not know and know Riau Batik, people only know and are familiar with batik from Java so that interest in Riau Batik is low. For this reason, it is necessary to have a place for the community to learn about Riau batik and a place for batik to grow, develop and maintain its sustainability, namely the Batik House. The design of the batik house uses an eco-tech architectural theme. Through this theme, it is hoped that the design of the Riau Batik House building can adapt to the natural, social and local cultural environment, survive and function with the times as well as Batik crafts that still survive today, involve technology to support ecological architectural design and provide comfort aspects. for users. Keywords: Batik, Riau Batik, Eco-Tech Architecture